Empirical Equation of CO2 Corrosion with the Presence of Low Concentrations of Acetic Acid at Turbulent Flow Conditions - che ismail, mokhtar; fatah, martin choirul (Maney Publishing, 2010)
The presence of organic acid species in formation water of oil and gas reservoirs has long been suspected to contribute to the corrosivity of CO2 corrosion. The effect had been regarded as secondary until new findings in the 80’s and 90’s revealed the increase in corrosion rate in CO2 environment with the presence of acetic acid species. This is potentially detrimental as most of the predictive models used in corrosivity assessment of the field do not incorporate considerations of the effects of acetic acid species. This paper presents experimental corrosion rates of carbon steel in CO2 environments with the presence of acetic acid species in the turbulent flow conditions, based on linear polarization resistance (LPR) analysis. The experimental corrosion rates are compared with the corrosion rates predicted by industrial predictive models such as NORSOK and Cassandra. Based on the findings, we can conclude that acetic acid species increase the corrosion rate of carbon steel in CO2 corrosion and standard predictive models do not capture this effect. An empirical equation is proposed to cater for the presence of low concentrations of acetic acid in CO2 corrosion under turbulent conditions.